Antibody-Mediated Targeting of the FGFR1c Isoform Increases Glucose Uptake in White and Brown Adipose Tissue in Male Mice - Lewis, Jo E. (Endocrinology, 2017)
The increased prevalence of obesity and its cardiometabolic implications demonstrates the imperative to identify novel therapeutic targets able to effect meaningful metabolic changes in this population. Antibody-mediated targeting of fibroblast growth factor receptor 1c isoform (FGFR1c) has been shown to ameliorate hyperglycemia and protect from diet- and genetically-induced obesity in rodents and nonhuman primates. However, it is currently unknown which tissue(s) contribute to this glucose-lowering effect. Thus, to elucidate this effect, we treated euglycemic mice with H7, a monoclonal antibody that selectively targets FGFR1c, and used whole-body positron emission computed tomography with a glucose tracer ((18)F-fluorodeoxyglucose). Treatment with H7 increased basal glucose uptake in white adipose tissue (WAT), brown adipose tissue (BAT), the brain, and liver but reduced it in the quadriceps muscles. Consequentially, blood glucose was significantly reduced in response to treatment. Under insulin-stimulated conditions, the effects of H7 were maintained in WAT, BAT, liver, and muscle. Treatment with H7 decreased triglyceride (TG) content and increased adipose TG lipase content in white adipose tissue, while increasing activation of acetyl coenzyme A carboxylase, suggesting futile cycling of TGs, albeit favoring net hydrolysis. We demonstrated, in vitro, this is a direct effect of treatment in adipose tissue, as basal cellular respiration and glucose uptake were increased in response to treatment. Taken together, these data suggest that antibody-mediated targeting of FGFR1c exerts its powerful glucose-lowering efficacy primarily due to increased glucose uptake in adipose tissue.